Tinjauan Hukum terhadap Penyelesaian Sangketa Kredit Macet di Bank Umum di Indonesia - Bambang Fitrianto; Siti Nur Raihani; Yola Fifilyan Salam; Joito Rajagukguk; Yusnidar Sitorus; Suvanji Binsar Aritonang (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study examines the legal aspects of resolving non-performing loan disputes in commercial banks in Indonesia. Non-performing loans are a crucial issue impacting bank financial stability and the protection of debtor and creditor rights.This study examines banking regulations and contract law governing non-performing loan resolution, including credit restructuring mechanisms, mediation, arbitration, and litigation. The analysis includes the Banking Law, Financial Services Authority (OJK) regulations, and judicial practices related to non-performing loan disputes. The results indicate that resolving non-performing loan disputes requires a comprehensive and equitable legal approach, with an emphasis on consumer protection and legal certainty for banks.Furthermore, alternative out-of-court dispute resolution methods such as mediation and arbitration are considered effective in expediting settlements and reducing the burden on the courts. However, challenges remain in implementing consistent and transparent regulations. This study recommends strengthening regulations and increasing the capacity of dispute resolution institutions to support optimal and equitable non-performing loan resolution in Indonesia.